(untitled) (Communications in Computational Physics, 2018)
This work addresses the nonlinear dynamic behavior of different electrostatic micro-tweezers, a micro electric actuator. This actuator, a cantilever beam electrostatic micro-tweezers, has been extensively used in micro-electro-mechanical systems (MEMS). The importance of micro electric actuators manufactured is higher than the other part of MEMS since it is the power source of the entire micro-electro-mechanical systems. In actual operation, the instability and bad dynamic characteristics of the electric actuators will cause larger displacement mobility error, such as transport behavior and response procedures failure, etc., and even damage the micro-electro-mechanical systems. To improve the actuator dynamic displacement accuracy, the dynamic behavior in the electric actuator system must be studied, especially for nonlinear dynamic behavior of system. In this work, the differential quadrature method (DQM) was employed to solve the problem of nonlinearity in the equation of motion. The results reveal that the proposed DQM model can be used to simulate the nonlinear behavior of the micro-tweezers efficiently. Micro-tweezers of various shapes were studied to examine the feasibility of applying the DQM in analyzing their nonlinear responses. The simulated results agree very closely with the calculated and experimental data in the literature.